Pengaruh Faktor-Faktor Produksi terhadap Pendapatan Petani Kelapa Sawit di Kecamatan Muara Batangtoru - Novita Aswan; Yulia Windi Tanjung (Seminar Nasional Lahan Suboptimal, 2020)
Aswan N, Tanjung YW. 2020. The Influence of production factors on oil palm farmers' income in Muara Batangtoru district. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The research had done in Terapung Raya Village, Muara Batangtoru District, South Tapanuli Regency on 20 oil palm farmers. The researcher applied an interview system and filled out a questionnaire to collect data from 20 oil palm farmers who were selected based on predetermined criteria. The research objective is to determine the effect of production factors on the income of oil palm farmers in floating village and to see other constraints that affect the production and income of other farmers. The data used in this research are secondary data and primary data which come from interviews and farmer questionnaires as well as other supporting data from literature studies and related agencies. Production factors that form the basis of this research are the amount of oil palm production, land area, age of oil palm plantations, maintenance costs of oil palm and the selling price of oil palm. The results showed that on average the farmers in Terapung Raya Village were still of productive age with adequate levels of education and their own land. From the results of data analysis, production factors have an influence on the income of oil palm farmers. Production factors that have a significant effect on farmers' income are the amount of production and the selling price of oil palm. Meanwhile, other factors such as land area owned by farmers, plant age and maintenance costs do not have a significant effect on farmers' income in Terapung Raya Village, Muata Batangtoru District.